The function of the proneural genes achaete and scute in the spatio-temporal patterning of the adult labellar bristles of Drosophila melanogaster. - Ray, K.; Rodrigues, V. (Roux's Archives of Developmental Biology, 1994)
The sensory precursors for labellar taste bristles develop from the labial disc in three distinct temporal waves occurring at 0 h, 8 h and 14 h of pupal development. In each temporal wave, transcripts for the achaete (ac) and scute (sc) genes are expressed in overlapping patterns in cells of the disc epithelium prior to the appearance of sensory mother cells (SMCs). No bristles form in mutant flies in which the ac and sc genes are absent. When the sc gene alone is deleted, a set of seven bristles fail to form. Pulses of ubiquitous sc (+) expression during pupal development, in a strain mutant for both ac and sc, can result in flies with all the labellar bristles at their correct positions. sc (+) pulses at times corresponding to the initiation of each of the waves of SMC specification in the disc was sufficient to restore bristle pattern. Bristles were not induced at ectopic positions and times as a result of the ubiquitous expression of sc (+). These results suggest that the proneural genes ac and sc do not themselves set the pattern of the labellar bristles. Instead, they are required for the elaboration of the pattern set by other gene products. We also show that the formation and positioning of the later waves of bristles can take place even in the absence of bristles normally specified earlier.